Imerisms in Zurab Kukhianidze’s Poetry - Danelia, Vaja (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
In literature worldwide, authors often draw from the rich reservoir of colloquial language, resurrecting forgotten terms and inventing new ones, thereby enriching the tapestry of their literary expression. This holds true for Georgia as well. Zurab Kukhianidze, hailing from Kutaisi, emerges as a fascinating creator whose poetic language resonates across different generations and tastes, thus piquing the keen interest of researchers. This paper aims to delve into the role of dialectical elements in Zurab Kukhianidze’s poetic universe, particularly focusing on Imerisms. These linguistic elements not only infuse a natural cadence into the narrative, evoking the ethnic hues of his native region and portraying local realities with profound artistic effect, but they also serve as windows into the writer’s innermost thoughts and emotions. As poet Otar Mamforia beautifully reflects, „His poems are akin to paths of the soul, where through their protective verses, one can hear the echoes of Georgian soil.“ Within Zurab Kukhianidze’s poetry, a significant role is bestowed upon angular speech, predominantly through Imerisms. This emphasis is unsurprising given that the essence of his poetry is deeply rooted in his love for the land of his birth and upbringing — Imereti. As he muses in conversation with an Imeretian peasant, „There is one ‘Ime’!... But which one? ‘I’m here.“ Hence, Imerisms organically permeate his work, ensuring lexical diversity and authentically capturing the dialectical essence of this distinctive region.